Method validation and development of analysis of Drotaverine and Mefenamic acid by RP-HPLC method (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
A fast, sensitive, and reliable RP-HPLC method involving Waters HPLC System Model NO.2690/5  with PDA detector was developed and validated for the determination and quantification of Drotaverine and Mefenamic Acid . Chromatography was performed on the Inertsil -ODS C18 (250 x 4.6 mm , 5 μ) column using filtered and mixed Degassed Methanol : Acetonitrile (80:20) as a mobile phase with a flow rate of 1.0 ml / min and selected injection volume 20μl, an effluent of 280nm. Retention times for Drotaverine 2.955min, and Mefenamic Acid 3.538 min. The proposed method is accurate, precise, specific and rapid for estimation of Drotaverine and Mefenamic Acid in bulk and pharmaceutical dosage form.
Keywords: Drotaverine; Mefenamic Acid; RP-HPLC; ODS; Acetonitrile; Methanol